Caracterización de residuos sólidos urbanos de la ciudad de Guaranda. - Alarcón Gualuntuña, María Isabel (2024)
This research studies the characterization of urban solid waste in the city of Guano, La Matriz parish, implementing three different methodologies. For the urban and socioeconomic characterization, the technique of Arellano et al. (2012) was used. Similarly, for determining the study sample, the method of Arellano & Cabezas (2014) was applied. The last technique employed by Arellano et al. (2013) was based on the quantification of per capita production (PPC), loose densities, and components of urban solid waste. Within the city of Guano, La Matriz parish, 213 blocks with residential/mixed land use were identified, comprising four socioeconomic strata. Stratum A represents the class with the highest purchasing power at 2.35%, stratum B at 36.15%, stratum C at 50.23%, and stratum D at 11.27%. The sampling of urban solid waste was conducted in 76 households over 7 consecutive days to determine per capita production, densities, and components. The PPC for stratum A is 0.55 kg/person/day, for stratum B is 0.63 kg/person/day, for stratum C is 0.583 kg/person/day, and for stratum D is 0.56 kg/person/day, resulting in a weighted per capita production of 0.60 kg/person/day for the city of Guano, La Matriz parish. The average loose density for stratum A is 125.53 kg/m³, for stratum B is 208.70 kg/m³, for stratum C is 262.84 kg/m³, and for stratum D is 210.82 kg/m³, determining a weighted loose density of 234.18 kg/m³ for the city of Guano, La Matriz parish. In the physical composition of urban solid waste, organic waste predominates at 65.43%, followed by potentially recyclable waste (glass, PET bottles, cardboard, paper, etc.) at 21.25%. Similarly, potentially recyclable waste for the future represents a generally low percentage at 0.69%, and finally, 12.63% corresponds to disposable Waste.